Implantação de Estação Solarimétrica e de Sistema Supervisório com Scadabr e Plataforma IoT em usina fotovoltaica na UNILAB-CE - Pontes, Wyara Maria Carlos Souza (2021)
In a paradigm shift in the electric power generation segment, private institutions, utilities and customers are installing distributed generation units to produce electricity closer to their end use. In Brazil, the growth of distributed generation from renewable resources, especially solar photovoltaic, has grown since the implementation of net-metering measurement policies in 2012. The performance of photovoltaic systems is mainly influenced by the incident radiation levels and the temperature air, which in turn influences the temperature of the photovoltaic module. Solarimetric stations and supervision and monitoring systems are of fundamental importance for the acquisition and analysis of data that assist in decision making and in the management of generation plants. This work presents the implementation of a commercial solarimetric station and supervisory systems based on SCADABR and through the IoT monitoring platform of the solarimetric station and the 254.2 kWp photovoltaic solar minigeneration plant, installed on the Auroras campus of the Universidade da International Integration of Afro-Brazilian Lusophony - UNILAB, in Ceará. The ScadaBR supervisory system is capable of remotely monitoring the solarimetric station and the generation plant. For remote access by mobile device, a prototype of a low-cost data acquisition and communication system based on an electronic IoT platform for the solarimetric station was developed. In addition to the development of a monitoring system via the website, via an application for mobile devices and through Scada, the present work also presents performance analysis of the data acquisition prototype, using the solarimetric station as a reference. The supervision of the solarimetric station and the generation plant allowed continuous and real-time monitoring of the equipment to verify performance.